(untitled) (Journal Of Educational and Psychological Researches, 2016)
The research aims to know The Effect Of Flexible Grouping Strategy and Three Step Interview strategy on achievement of the history material among student of the first literary class, The Researcher used the experimental design of the two experimental groups and the control group and with post test, researcher group (a) represent the experimental group taught according the Flexible Grouping Strategy , and Division (c) to represent the second experimental group which studied according Three Step Interview strategy and Division (b ) to represent the control group taught in the traditional method, the number of students (99) students of (33) female students in each division. The reward research groups in the variables: age, intelligence and, Prior knowledge. The researcher were verified psychometric characteristics of the instruments, and used, Analysis of variance (ANOVA ) and Tukey test used for data processing , The results showed superiority of the two experimental groups to the control group, also showed no difference statistically significant between the two experimental groups, which studied according to the flexible groups and Three Step Interview in the achievement of the students of the first literary class..